Clinical features and prognostic predictors in patients with rheumatic diseases complicated by Pneumocystis pneumonia. (September 2022) - Huang, Yi-Min; Lu, Cheng-Hsun; Cheng, Chiao-Feng; Shen, Chieh-Yu; Hsieh, Song-Chou; Li, Ko-Jen; Chien, Jung-Yien; Hsueh, Po-Ren; ,
HIGHLIGHTS: Pneumocystis pneumonia (PCP) is a fatal complication in patients with rheumatic disease. The dosage of adjunctive corticosteroids for PCP is debated in rheumatic diseases. The optimal cutoff point of adjunctive corticosteroid dosage was 0.6 mg/kg/day. An adjunctive corticosteroid dosage ≥0.6 mg/kg/day was a risk factor for mortality. ABSTRACT: Objectives: To investigate the clinical outcomes and risk factors of mortality in patients with rheumatic diseases complicated by Pneumocystis pneumonia (PCP). Methods: Between November 2015 and April 2021, patients with rheumatic diseases with PCP in a tertiary referral hospital were retrospectively enrolled. The diagnosis of PCP requires the fulfillment of clinical, radiographic, and microbiological criteria. Factors associated with in-hospital, 30-day, and 90-day mortality were evaluated. Results: A total of 128 patients with rheumatic diseases who had a positive quantitative polymerase chain reaction assay for Pneumocystis jirovecii were screened, and 72 patients were included in the final analysis. The median (interquartile range [IQR]) pneumonia severity index (PSI) was 101.5 (77.0-132.0). The median (IQR) adjunctive corticosteroid dosage was 0.6 (0.4-0.9) mg/kg/day prednisolone equivalent. The receiver operating characteristic curve analysis showed that the optimal cutoff point of median adjunctive corticosteroid dosage was 0.6 mg/kg/day to predict in-hospital, 30-day, and 90-day mortality. In the multivariable logistic regression analysis, median adjunctive corticosteroid dosage ≥0.6 mg/kg/day and PSI >90 were independent factors of in-hospital, 30-day, and 90-day mortality. Conclusion: A median adjunctive corticosteroid dosage of ≥0.6 mg/kg/day might be associated with mortality in patients with rheumatic diseases complicated by PCP.